Incidence of Postpartum Depression and Associated Risk Factors in Antenatal Women: A Cohort Study - Eshani Pandey; Sumit Mehta; Shobit Garg; Sanjibani Panigrahi; Anmol Suneja (Annals of Indian Psychiatry)
Background: The incidence of postpartum depression (PPD) varies across cultures, regions, and communities, and there are very few studies addressing this issue, henceforth making it difficult to estimate the actual burden of the disease. Aims: The aim of this study was to evaluate the incidence and identify potential risk factors for PPD in a cohort of antenatal women. Methods: This study conducted in a tertiary hospital included 105 participants in their second or third trimester of pregnancy. Relationship with and support from the family were assessed. The scales applied were the Perceived Stress Scale, Ardell Wellness Stress Scale, State-Trait Anxiety Inventory, and Pittsburgh Sleep Quality Index. Participants were followed up 4 weeks postnatally. They were asked about the gender of their baby, and the Edinburgh Postnatal Depression Scale (EPDS) was applied. PPD was evaluated using the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition criteria and International Classification of Diseases-10 criteria. Results: Of the 105 participants, 6 were lost to follow-up. Among the 99 women, an EPDS score of ≥10 was identified in 17 women who were diagnosed with PPD. The risk factors according to our study were sleep disturbances, state anxiety, stress, and obstetrical complications antenatally and female sex of the newborn. These risk factors are likely to be interactive as well as multiplicative in effect. Conclusion: The study shows a high prevalence of PPD in Indian mothers. There is enough evidence suggesting that intervention for PPD is crucial for the care of the mother as well as for the well-being of the infant, hence an integrated approach is required for its screening.